THE INFLUENCE OF TECHNICAL DEVIATIONS OVER EFFORTS FROM A 4R SPHERICAL QUADRILATERAL MECHANISM - Nicolae PANDREA; Ion BULAC (Fiabilitate şi Durabilitate)
In the present paper is mechanically defined the notion of technical deviation (geometrical) through a matrix of pluckerian coordinates and those influence over the efforts from the 4R spherical quadrilateral mechanism elements.